The Effects of Pregnancy and Nutritional Stress on Fat Partitioning in The Body of Ewes - I. K. Saka; J. M. Thompson; G. N. Hinch; P. Raynolds (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy